Non-steroidal anti-inflammatory drugs, Cyclooxygenase-2 inhibitors and paracetamol use in Queensland and in the whole of Australia - Tett Susan E; Barozzi Nadia (BMC, 2008)
Abstract Background Cross national drug utilization studies can provide information about different influences on physician prescribing. This is important for medicines with issues around safety and quality of use, like non selective non-steroidal anti-inflammatory drugs (ns-NSAIDs) and cyclo-oxygenase-2 (COX-2) inhibitors. To enable comparison of prescription medicine use across different jurisdictions with a range of population sizes, data first need to be compared within Australia to understand whether use in a smaller sub-population may be considered as representative of the total use within Australia. The aim of this study was to compare the utilization of non selective NSAID, COX-2 inhibitors and paracetamol between Queensland and Australia. Method Dispensing data were obtained for concession beneficiaries for Australia for ns-NSAIDs, COX-2 inhibitors and paracetamol subsidized by the PBS over the period 1997-2003. The same data were purchased for Queensland. Data were converted to Defined Daily Dose (DDD)/1000 beneficiaries/day (World Health Organization anatomical therapeutic chemical classification, 2005). Results Total NSAID and paracetamol consumption were similar in Australia and Queensland. Ns-NSAID use decreased sharply with the introduction of COX-2 inhibitors (from approximately 80 to 40 DDD/1000 beneficiaries/day). Paracetamol was constant (approximately 45 DDD/1000 beneficiaries/day). COX-2 inhibitors consumption was initially higher in Queensland than in the whole of Australia. Conclusion Despite initial divergence in celecoxib use between Queensland and Australia, the use of ns-NSAIDs, COX-2 inhibitors and paracetamol overall, in concession beneficiaries, was comparable in Australia and Queensland.